Analytical modeling of subthreshold characteristics of ion-implanted symmetric double gate junctionless field effect transistors - Singh B.; Gola D.; Singh K.; Goel E.; Kumar S.; Jit S. (My University, 2025)
This paper reports a 2D analytical model for the subthreshold current and subthreshold swing (SS) of ion-implanted Double-Gate Junctionless Field Effect Transistors (DG-JLFETs) with a vertical Gaussian-like doping profile. The effects of gate length, straggle parameter, oxide thickness, channel thickness, and peak doping concentration on subthreshold current and subthreshold swing have been demonstrated. The model results are validated with the simulation data obtained by 2-D TCAD ATLASTM device simulator. Finally, the performance of a CMOS inverter using the DG-JLFET device has been investigated through ATLASTM TCAD mixed mode circuit simulations. © 2016 Elsevier Ltd